The Phylogenetic Relationship Among Varieties of Lansium domesticum Correa Based on ITS rDNA Sequences - Laila Hanum; Rina Sri Kasiamdari; S. Santosa; R. Rugayah (Universitas Gadjah Mada, 2013)
Lansium domesticum Corr. with vernacular name in Indonesian duku has been reported containingtherapeutic bioactive compounds, and some of these compounds shown to be potent antitumor, anticancer,antimalaria, antimelanogenesis, antibacteria, and antimutagenic activities. This plant is commonly known asduku, kokosan and langsat by the local community in Indonesia. The morphological appearance of all varieties isnearly the same, and identifi cation of the varieties is very diffi cult for growers. Variation of DNA sequences ofthe ITS (Internal transcribed spacer) region can be used as a molecular character to determine the phylogeneticrelationship of different varieties of L. domesticum. The aims of this study were to determine taxonomy status ofduku, kokosan, and langsat, also phylogenetic relationship among varieties of L. domesticum based on ITS rDNAsequencing. DNA was isolated from leaves of plant and then amplifi ed using F1 and R1 primers. Nucleotidesequences were identifi ed using Sequence Scanner Software Programm version 1.0, nucleotide sequences from18S, ITS1, 5.8S, ITS2 and 26S region, that has been mergered using EditSeq and SegMan in software Suite forSequence Analysis DNASTAR Lasergene DM version 3.0.25. The results of study showed that DNA fragmentsranging in size from 782-810 bp. Different pattern of DNA fragments indicated polymorphism among duku,kokosan, and langsat. Based on the results of the ITS rDNA sequencing and phylogenetic tree analysis. Itwas determined that Lansium and Aglaia are a separated genus with the similarity index value of 0.98. Duku,kokosan and langsat were divided into two cluster, namely cluster kokosan-langsat and cluster duku with thesimilarity index value of 0.996. Keywords : Phylogenetic relationship, ITS region, L. domesticum, duku, kokosan, langsat